MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN MELALUI METODE BERCERITA DENGAN BIG BOOK DI TK MELATI/ABA 005 KECAMATAN KUOK KABUPATEN KAMPAR - Ramona Sintya Dewi; Isjoni Isjoni; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in the ability to speak in children aged 5-6 years through storytelling with the big book in kindergarten Bed / ABA 005 Kuok District of Kampar regency. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children in group B which has 15 children in kindergarten Melati. The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the method of storytelling with a big book can improve the ability to speak in children ages 5 -6 years. It can be seen from the increase in the average percentage of the ability to speak children in the first cycle by 53.7% which is the criteria began to develop (MB) and increased by 50, 2% in the second cycle be 80.7% which is very good at developing criteria (BSB). Thus, the method storytelling with big media book can improve listening skills of children ages 5 -6 years in kindergarten Bed / ABA 005 Kuok District of Kampar regency.Keywords : Speech, Storytelling Method with Media Big Book